2012
DOI: 10.1007/s10490-011-9280-6
|View full text |Cite
|
Sign up to set email alerts
|

The distinctive effects of dual-level leadership behaviors on employees’ trust in leadership: An empirical study from China

Abstract: The loss of trust within and between organizations has become serious worldwide, especially in China. In this study, we seek to explain why as well as how leaders at two different levels (i.e., the top management and the supervisory levels) affect employees' trust in leadership at the two levels distinctively, especially in the context of China as an emerging economy. Adopting the perspective of multi-level social exchanges within organizations, we develop a dual-level model with perceived organizational suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 86 publications
(125 reference statements)
2
34
0
Order By: Relevance
“…Riskaverse people will use this communication type with caution or never use it (Lin & Johnson, 2015). This risk-avoidance tendency might be more aggravated in the Chinese context of this study which values harmony and relationships (Bai, Han, & Harms, 2016;Bai, Harms, Han, & Cheng, 2015;Bai, Li, & Xi, 2012). Thus, even if encouraged by organizational systems, prohibitive voice is less likely to happen in the whole team.…”
Section: Theoretical Implicationsmentioning
confidence: 84%
“…Riskaverse people will use this communication type with caution or never use it (Lin & Johnson, 2015). This risk-avoidance tendency might be more aggravated in the Chinese context of this study which values harmony and relationships (Bai, Han, & Harms, 2016;Bai, Harms, Han, & Cheng, 2015;Bai, Li, & Xi, 2012). Thus, even if encouraged by organizational systems, prohibitive voice is less likely to happen in the whole team.…”
Section: Theoretical Implicationsmentioning
confidence: 84%
“…Comparatively, little is known on the relationship between transformational leadership and POS. Whereas several authors reported a positive relationship between these two constructs (Al-Hussami, 2009;Bai et al, 2012;Cho et al, 2011;Connell et al, 2003;Hyatt, 2007), most of these articles did not explicitly focus on this relationship. As a result, the rationale underlying this relationship has not been developed and the boundary conditions in which transformational leadership is more (or less) effective in predicting POS have not been examined.…”
Section: Mediating Role Of Pos In the Transformational Leadership Effmentioning
confidence: 99%
“…Using a multi-foci approach, Bai, Li, and Xi (2012) found that transformational leadership leads to better followers' performance at the top management and supervisory levels. The relationship at the top management level is mediated by perceived organizational support and trust in top management team, whereas the relationship at the supervisor level is mediated by leader-member exchange and trust in supervisor.…”
Section: Four Emerging Themesmentioning
confidence: 99%
“…Also, empirical evidence in the Western context suggests that micro-level rather than macro-level social exchange is more likely to shape employees' organizational citizenship behavior (OCB) (Dirks & Ferrin, 2002). Yet, based on the sample from China, Bai et al (2012) found that, among other things, both macro-level and micro-level exchange (i.e., employees' trust in top management team and trust in supervisor) were related to OCB. This result suggests that in the Chinese context, employees may translate their trust in their immediate supervisors into behavioral reactions towards their organizations, perhaps due to collectivistic values (Chen, Tsui, & Farh, 2002).…”
Section: Four Emerging Themesmentioning
confidence: 99%